Unlocking Economic Potential - Shantal Kirabo Katimbo (Uganda Christian University, 2025)
This work addresses the critical challenge of safeguarding Uganda's Traditional Medicine (TM). While TM is a vital healthcare resource and a cornerstone of the nation's cultural heritage, its significant economic potential remains largely unrealized. Despite Uganda's existing Intellectual Property (IP) policies and international commitments, key gaps persist. These include slow legal operationalization and a fundamental incompatibility between conventional IP systems and the communal, orally transmitted nature of traditional knowledge. This situation is worsened by a widespread lack of IP awareness among traditional healers and insufficient documentation of their knowledge. This deficit in IP awareness directly impedes equitable commercialization and heightens the threat of biopiracy. Foreign entities can exploit these vulnerabilities to appropriate communally owned knowledge without compensation, eroding indigenous sovereignty and cultural identity. The core purpose of this study is to propose effective IP protection strategies for Traditional Herbal Medicine in Uganda. This aims to ensure both economic empowerment and the enduring preservation of cultural heritage. It advocates for adapting successful global models to Uganda's unique socio-cultural and economic context through expedited policy implementation, targeted IP capacity building, and robust benefit-sharing mechanisms.
Undergraduate Dissertation